THE EFFECT OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON FIRM VALUE THROUGH FINANCIAL PERFORMANCE AS MEDIATION VARIABLES IN PALM OIL PLANTATION COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Noviantika, Lessy; Erlina, Erlina; Aulia Adnans, Abdhy (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the effect of Corporate Social Responsibility (CSR) Disclosure and Good Corporate Governance (GCG) proxied through the Audit Committee, Independent Commissioners and Institutional Ownership on Firm Value through Financial Performance as a mediating variable. The population of this study is all oil palm plantation companies listed on Indonesia Stock Exchange for the period 2016-2020. The sample used in this study amounted to 11 companies. This type of research uses quantitative research methods. Data analysis using Path Analysis approach, with analysis tools using SPSS. The results show that institutional ownership has a negative effect on firm value (Tobin's Q). Audit Committee, CSR Disclosure and Financial Performance have no effect on Firm Value. Independent Commissioner has a positive effect on Firm Value. Institutional ownership has a positive effect on financial performance. However, the Audit Committee, Independent Commissioner and CSR Disclosure have no effect on Financial Performance. Based on the results of the mediation test, it shows that Financial Performance is able to act as a mediating variable between CSR Disclosures, Audit Committees and Institutional Ownership on Firm Value, but Financial Performance is not a mediating variable in the relationship between Independent Commissioners and Firm Value.